The impact of capital structure on financial performance of companies listed in Bursa Malaysia / Farina Hamiza Mohd Fadil - Mohd Fadil, Farina Hamiza (Faculty Of Business Management, 2017)
This study is to look at the influence of the capital structure on the financial performance of companies listed at the Bursa Malaysia Stock Exchange. The sample of the study about was ten companies from industrial sector. The film's overall performance (the dependent variable) was measured by way of return on asset (ROA), retum on equity (ROE) and incomes per share (EPS) whilst capital structure (the independent variable) was measured with the aid of short term debt to total asset (STDTA) and long term debt to total asset (LTDTA). This study covered a period of 11 years (2006-2016). Comprehensive earnings and financial role had been analyzed in this study and the exfracted data used to be analyzed via using eviews9 statistical software. (STDTA) negatively and significantly affect the performance in case of ROA and ROE. While in case of EPS, (STDTA) also negatively but impact was insignificant. Based on the results above, (LTDTA) negatively and significantly affect the firm performance ROA. Besides that, (LTDTA) also shows negative but insignificant in case of ROE. Lastly, the capital structure (LTDTA) had a positive and significant impact on firm performance which measured by EPS.